Dynamic color communication. (December 2015) - Hutton, Pierce; Seymoure, Brett M; McGraw, Kevin J; Ligon, Russell A; Simpson, Richard K
Highlights: Animal colors are dynamic in both space and time. Colors can be considered and studied in many of the same ways as animal behaviors. We review recent findings in these emerging areas of dynamic color communication. We highlight the interactive dynamics of color signaling between senders and receivers. We need a better understanding of neural/sensory plasticity in color vision. Abstract : Animal behaviors are dynamic in both space and time, and this variation is the raw material for exceptional behavioral adaptations in the animal kingdom. Here we argue that this same dynamism characterizes color signals in nature and that comparable approaches, both conceptually and methodologically, should be taken to comprehensively assess the production, perception, function, and evolution of dynamic animal colors. We review and synthesize recent findings in these emerging areas of color research and highlight the complex and interactive dynamics of color communication between senders and receivers. We also advance opportunities for new areas of research, especially centered on visual and neural plasticity of color reception as well as the intricate signaling interactions between co-expressed display behaviors and colors.